EXISTENCE OF ARTIFICIAL INTELLIGENCE FOR AUTOMATION OF CONTRACT FORMATION BASED ON THEORY CONTRACT LAW - Prastyanti, Rina Arum; Tengpongsthorn, Wuthichai (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Artificial intelligent technology gives rise to contract automation. In contract law, intention is one of the principles of making contracts. In addition, contracts must also be formed based on the results of discussions and meetings of minds which result in accordance with the wishes or desires so that they can be included in a contract. Contract automation through Artificial Intelligent can be called a conflict of fundamental requirements for contract formation. The general contract law that has emerged through Artificial Intelligence does not take into account mental state and does not examine the true thoughts or intentions of the parties. Based on the explanation above this research aim is to find out Artificial Intelligent in contract formation based on the theory of contract law. Law is conceptualized as a norm or rule that applies in society and becomes a reference for everyone's behavior in normative legal research with the goal of discovering facts that are used as research data relating to the existence of artificial intelligent for automation og contract formation based on contract theory contract law. This research method employs a statutory approach involving a review of all relevant laws and regulations. This type of research is also known as descriptive-analytical research because the findings are presented descriptively and analytically, so this method was chosen The findings research, contracts formed using artificial intelligence are not legally binding, even if the technology underlying them advances. The technology that underpins them advances. Currently, despite the fact that computer programs or Artificial Intelligence create contracts. There is no authority to support any legal distinction based on the level of human involvement or program complexity. If the common law of contract is to introduce a distinction depending on how the theory of contract law is based on the appearance of the intent of a person or legal entity in making the statements in the contract as intended."Unintended contracts," or contracts that do not arise from the intention of a person or legal entity and are not based on the fairness and trust theory, will be prohibited